Effect of Cold Chain Logistic Interruptions on Lipid Oxidation and Volatile Organic Compounds of Salmon (Salmo salar) and Their Correlations With Water Dynamics - Yu, Ying-Jie; Yang, Sheng-Ping; Lin, Ting; Qian, Yun-Fang; Xie, Jing; Hu, Changli (Frontiers in Nutrition, 2020)
Lipid oxidation and water migration are important factors in the quality changes of aquatic products. This study investigated the relationship between water migration and lipid oxidation in salmon filets under four different storage conditions (control: 0°C; T1: 4°C; T2 and T3: two temperature fluctuation groups) by detecting thiobarbituric acid–reactive substances, changes of fatty acids, and volatile organic compounds (VOCs), and other quality indicators including redness, microorganism, total volatile basic nitrogen (TVB-N), and water-holding capacity (WHC) were also measured. The results of low-field nuclear magnetic resonance (LF-NMR) showed that more trapped water (T22) turned to form free water (T23) in groups suffering temperature fluctuations. A more significant decrease in fatty acids was found in T2 and T1 groups, especially oleic acid (C18:1n9c), linoleic acid (C18:2n6c), and palmitic acid (C16:0). The VOCs with off-flavors (1-penten-3-ol, 2-penten-1-ol, (Z)-, 1-octen-3-ol, hexanal) in the groups suffered from simulated cold chain interruptions increased faster than the other two groups during storage. T22 was negatively correlated (p < 0.05) with stearic acid (C18:0), 1-penten-3-ol, hexanal, and nonanal, whereas T23 was positively correlated with 1-penten-3-ol, hexanal, and heptanal. Therefore, the temperature fluctuation accelerated the loss of polyunsaturated fatty acids and the increase of unpleasant odors related to water migration.